Circular Economy and the Textile Industry in Paraguay. - VICTOR MELGAREJO (Población y Desarrollo, 2019)
Since the advent of the industrial revolution in the 19th century, the growth of our current economy is based on a linear production process of the product life cycle: raw material, production, consumption and disposal as waste. Every day, there is more consensus that the continued growth of the world population and consumption requires establishing a new production model less dependent on energy and raw materials, so that the planet's ecosystem can be regenerated. The capacity of the circular economy, as reparative and regenerative, aims to ensure that products, components and resources in general, maintain their unity and value. The methodology was documentary - bibliographic, mainly using literature from countries whose discussion is in vogue, belonging to the European Union bloc. In conclusion, it can be mentioned that, the circular economy is a potential generator of jobs, the relation with respect to the incineration of wastes from 1 to 100, that is, the incineration of waste generates a single job, while the same amount of waste, with recycling 100 jobs are generated. It is recommended to explore the circular economy further in order to contribute to the decrease in global warming.